2016
DOI: 10.1007/s11356-016-6714-1
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of nutrients and pesticides from small- and large-scale agriculture on the water quality of Lake Ziway, Ethiopia

Abstract: The area around Lake Ziway in Ethiopia is going through a major agricultural transformation with both small-scale farmers and large horticultural companies using pesticides and fertilisers at an increased rate. To be able to understand how this influences the water quality of Lake Ziway, water quality data was gathered to study the dynamics of pesticide concentrations and physicochemical parameters for the years from 2009 to 2015. Results indicate that for some physicochemical parameters, including pH, potassi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 18 publications
5
71
4
Order By: Relevance
“…The possible environmental risks have been demonstrated in other studies by Ramo et al (2016) and Teklu et al (2016) in Costa Rica and Ethiopia, respectively. There is, therefore, a need to perform environmental risk assessments of current pesticides use in Ghana to identify pesticides that pose the highest risks to the aquatic environment and to determine threshold levels of the pesticides that are protective of the environment.…”
Section: Farmers' Pesticides Use Practicesmentioning
confidence: 55%
“…The possible environmental risks have been demonstrated in other studies by Ramo et al (2016) and Teklu et al (2016) in Costa Rica and Ethiopia, respectively. There is, therefore, a need to perform environmental risk assessments of current pesticides use in Ghana to identify pesticides that pose the highest risks to the aquatic environment and to determine threshold levels of the pesticides that are protective of the environment.…”
Section: Farmers' Pesticides Use Practicesmentioning
confidence: 55%
“…() reported that climate change and irrigation on the CRV water system resulted in increased water abstractions. Other studies indicated agrochemicals (e.g., pesticides including DDT and spiroxamine) and heavy metals have been polluting Lake Zeway (Jansen & Harmsen, ; Yohannes et al., ; Teklu et al., ). Data are currently lacking regarding the status and impacts of urban wastes in the study area, although experiences from other towns in the country (e.g., Dessie; Bahir Dar; Hawassa) suggest urban wastes endanger the quality of the available water sources (Desta, ; Beyene et al., ; Tenagne, ).…”
Section: Resultsmentioning
confidence: 99%
“…A linearly increasing temperature was reported by Kassie (); subsequently, also increasing evapotranspiration in the CRV (Getnet et al., ) is a potential factor exacerbating the problem. Increasing demands for the limited water resources, and expansion of irrigated agriculture with intensive use of agrochemicals (Jansen & Harmsen, ) in the area, have also affected the water quality of Lake Zeway (Teklu et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…In Table 1, it can be observed that the values EC for both lakes are increasing, furthermore, a study conducted by Teklu et at. [19], the maximum EC value for Ziway lake was streteched to 1740µS/cm , the recent study conducted by Zigide and Tsegaye [20] the maximum value for Hawassa lake has been extended to 1999.4 µS/cm. Both lakes have shown the dramatic changes and exceeding the maximum permissible limit of 1000 µS/cm [17,18].…”
Section: Electrical Conductivity (Ec)mentioning
confidence: 93%
“…The pH values for the two lakes were analyzed in various years. As indicated in Table 1, the mean values of pH for Ziway Lake is in the range of MPL Ethiopian [17] and WHO standard [18], but a study by Teklu et al [19], the maximum values stretched to 9.0. In all years (Table 1), Lake Hawassa is not within the range of MPL.…”
Section: Phmentioning
confidence: 99%